Factors influencing IPO price in the short-term perspective between pre-IPO and post-IPO as an example of Indian stock market - Orak, A. (International School of Economics KAZGUU, Nur-Sultan, 2022)
This paper introduces reader with National Stock Exchange of India. This research will help to understand factors of share underperformance at the date of offering and first-day trading return in the range of pre-IPO and post-IPO. Previous research proved the fact that IPOs in India underpriced at first day of trading, there share price at the end of 1 st , 7 th , 15 th and 30 th trading day checked against the offer price. This study pursued short-term performance of post-IPO share prices. The objectives of the research:  measure the IPOs performance on first 30 trading days to confirm that whether investors can earn positive return on the close of these trading days.  assess the short-run performance of IPOs for firms listed at the National Stock Exchange.  to calculate market adjusted short-run returns, wealth relative index to get an in-depth knowledge about the IPOs performance.  to analyze the factors influencing price performance of IPOs. Sample were taken from 2021 and 2020 IPOs, there were 81 public offering in NSE, 62 of them have fitted sampling criteria. This research has found that IPOs in India were underpriced by an average 81% of 62 initially issued companies.
Keywords: IPO, price performance, index, return, market, ratios, underpricing, market capitalization, short-run analysis, regression model